Orthogenesis versus Darwinism - Popov, Igor (Springer International Publishing, 2018)
This book reviews the convoluted history of orthogenesis with an emphasis of non-English sources, untangles relationships between various concepts of directed evolution and argues whether orthogenesis has something to offer modern biology. Darwinism claims that evolution occurs by selection from an extensive random variability. An alternative viewpoint-that the material for variability is limited and organisms are predisposed to vary in certain directions-is the essence of evolutionary concepts that can be grouped together under the name of orthogenesis. Dating back to Lamarck, orthogenesis has existed in many guises. Branded as mystical and discarded as unscientific, it keeps re-emerging in evolutionary discussions.